PENGARUH KUALITAS PELAYANAN, SISTEM PERPAJAKAN, SANKSI DENDA, KEMAMPUAN FINANSIAL DAN PERSEPSI WAJIB PAJAK ORANG PRIBADI TERHADAP PENGGELAPAN PAJAK (TAX EVASION) - Islamiah Kamil (Unversitas Prof. Dr. Moestopo (Beragama), 2021)
This study aims to determine the magnitude of the influence of service quality, taxation system, fine sanctions, financial capacity and perceptions of individual taxpayers on tax evasion (tax evasion. Sample selection was carried out using the Convinience Sampling method. Respondents of the study were DKI Jakarta Regional Taxpayers. The sample used was 120 respondents. The sample technique used was multiple linear regression analysis in SPSS ver. 22. The results of this study partially prove that service quality has an effect on tax evasion. The tax system has an effect on tax evasion. Penalties have no effect on tax evasion. Financial capability has no effect on tax evasion. Perceptions of individual taxpayers do not affect tax evasion.